PEMANFAATAN AKTIVITAS ANTIMIKROBA SAPONIN DAUN PEPAYA PADA KEMASAN KELOBOT JAGUNG - Sri Wahyuningsih; Nugraha E. Suyatma; Harsi D. Kusumaningrum (Jurnal Teknologi dan Industri Pangan, 2016)
This study aimed to utilize saponins from papaya leaves as antifungal on maize husk packaging. Crude and semi-pure saponins were extracted from papaya leaves using Soxhlet and Ultrasonic-Assisted Extraction (UAE) methods. The total saponin contents were determined using UV-Vis spectrophotometry. Their ability to inhibit Aspergillus niger was tested by macrodillution method. The extracts were also applied to maize husk by soaking it for 5 minutes at concentration of 10, 20 and 25 mg/mL. The parameters observed were physical and mechanical properties (tensile strength and elongation), water vapor transmission rate (WVTR), total plate count (TPC) and mold and yeast counts (MYC) after 25 days of storage at room temperature (±28ºC). Drying of young papaya leaves using cabinet dryer resulted in the highest yield of crude saponin (12.96 ± 0.26%). Total saponin content in crude saponin extract was 115.43 mg/g, while in semi-pure saponin extract was 480.19 mg/g. Crude saponin and semi-pure saponin extract at concentration of 25 mg/mL could inhibit the growth of A. niger for 1.35 and 0.36 log CFU/mL, respectively after 24 hours. The WVTR test indicated that treatment with a concentration of 25 mg/mL of crude saponin extracts showed the lowest transmission. The addition of crude saponin and semi-pure saponin extract to the maize husk at the concentration of 10, 20 and 25 mg/mL was able to inhibit the microbial growth, represented by constant number in TPC and MYC for 25 days storage. This study showed that crude saponin and semi-pure saponin extract could improve the functional properties of maize husk as packaging materials.